Analysis of the economic development of the East Kazakhstan region (Journal of Economic Research & Business Administration, 2022)
One of the main tasks of the state is to ensure the uniform development of the country as a whole.This can be achieved by equalizing the socio-economic development of the regions. The purposeof the analysis of the economic development of the region is to identify the existing imbalances andunused economic potential of self-development of the region for further substantiation of options forthe strategy of economic development of the region. The main purpose of the integrated assessment ofthe regions of Kazakhstan, the analysis of the economic development of the East Kazakhstan region isto substantiate the need and find ways to strengthen it to determine the level and potential for furthersustainable economic development of each region of Kazakhstan. The use of a system of statisticalindicators in economic analysis; methods of charting and trends. The integrated assessment of theeconomic potential of the regions of Kazakhstan and its competitiveness was based on the final dataof state statistics and economic indicators, as they cover a wide range of different economic aspects inthe context of regions. The analysis is aimed, on the one hand, at identifying opportunities for increasingcomplexity in the economic development of the region, on the other hand, at assessing the conditionsfor its successful functioning in a market economy, based on the rational use of labor, material,natural and financial resources.Key words: regional economy, economic development, statistical indicators, economic problems,gross regional product, industry.